2021
DOI: 10.1002/ajpa.24301
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope evidence (Fe, Cu) suggests that sex, but not aging is recorded in rhesus macaque (Macaca mulatta) bone

Abstract: Objectives Here, we examine (1) if the sex‐related differences in iron (Fe) and copper (Cu) isotope ratios, represented as δ56Fe and δ65Cu values, respectively observed in humans exist in bulk occipital bone and incisors of male and female non‐human primates, and (2) if the variation of Fe and Cu isotope ratios, known to vary in human blood as a factor of age are similar in non‐human primate bone. Materials and Methods Isotope ratios were measured from the skeletal elements of 20 rhesus macaques (Macaca mulatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 84 publications
(144 reference statements)
1
2
0
Order By: Relevance
“…The observed difference between parous and nulliparous females is independent of age ( S8 and S9 Figs). Our results are in agreement with the recent work [ 40 ] showing that stable isotopes record sex-specific, but not age-specific changes in rhesus macaques. Work investigating the effects of parity on bone mineral content and density in rhesus macaques has also found that bone characteristics differ between age-matched parous and nulliparous females [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…The observed difference between parous and nulliparous females is independent of age ( S8 and S9 Figs). Our results are in agreement with the recent work [ 40 ] showing that stable isotopes record sex-specific, but not age-specific changes in rhesus macaques. Work investigating the effects of parity on bone mineral content and density in rhesus macaques has also found that bone characteristics differ between age-matched parous and nulliparous females [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…It was not until the late 1990's with the arrival of the rst commercialized multi-collector inductively coupled plasma mass spectrometry (MC-ICPMS), at the time the Plasma 54 (VG Elemental, now ThermoFisher Scientic, Bremen), that it was possible to achieve precise (0.02& per amu) Cu isotope ratio measurements. 2 The pioneering work of Maréchal et al 2 showed that the instrumental mass bias of MC-ICPMS can be corrected by a combination of standard/sample bracketing and elemental doping with Zn, which was further modied by using Ni 3,4 or Ga. 5,6 The overall consistency of the measurements of Cu isotope compositions by MC-ICPMS leads to the rapid development of applications in various elds such as cosmochemistry, 7,8 igneous, 9,10 ore, 11,12 sediment 13,14 and river 15,16 geochemistry, oceanography, 17,18 tracing atmospheric [19][20][21] and soil [22][23][24] pollution, assessing the diagnosis and prognosis of metabolic [25][26][27] and neurodegenerative [28][29][30] diseases, cancer, [31][32][33] but also in palaeoanthropology [34][35][36] and archaeology. [37][38][39] Prior to isotopic analysis, Cu needs to be separated from the matrix and further puried using ion-exchange chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…Because fractionation patterns differ with disease state 3 , Cu isotope ratios has been proposed as diagnostic indicators of Alzheimer’s disease 20 , 21 , breast, ovarian and colorectal cancer 27 , 28 as well as multiple diseases of the liver 9 , 26 , 29 , 31 . However, development of such diagnostics is presently hampered by numerous confounding variables including organisms’ sex 8 , 10 , age 13 , 19 , diet 32 , and menopausal state 15 , 33 .…”
Section: Introductionmentioning
confidence: 99%